The long-distance runner an autobiography - Richardson, Tony 1928-1991 (Morrow, 1993)
"Richardson writes beautifully of his quiet Yorkshire upbringing, surrounded by women he both loved and feared. He tells of his marriage to Vanessa Redgrave, the births of his daughters, his affair with Jeanne Moreau, his extraordinary life of travel, and his many famous and infamous friends." "Written with great wit, insight, and relentless honesty, The Long-Distance Runner is a record of a remarkably creative life - and may well be the most revealing and informative book ever written about modern theater and film."--BOOK JACKET
Keywords: Richardson, Tony <1928-1991>; Richardson, Tony -- 1928-1991; Motion picture producers and directors -- Great Britain -- Biography; Theatrical producers and directors -- Great Britain -- Biography; Autobiografie; Großbritannien; Biografie